The interplay of digital financial literacy, capability, autonomy in the financial decision-making in today's digital age - Wong, Zheng Wah (2024)
The objective of this study is to explore the interplay of digital financial literacy, financial capability, and financial autonomy in financial decision-making in today's digital age. Furthermore, the three independent variables, which are digital financial literacy, financial capability, and financial autonomy have been chosen to see whether they are associated with financial decision-making, which is the dependent variable. In this study, 318 copies of the Google Form survey were distributed to Malaysian Youth. IBM SPSS Statistics 26 was used to analyse and interpret the data collected from the Google Form survey. The data were analysed using descriptive analysis and inferential analysis. The results of this study showed that financial decision-making was affected by digital financial literacy, financial capability, and financial autonomy. Lastly, limitations, and recommendations for future research was discussed in later chapters.